2020
DOI: 10.1002/anie.201914667
|View full text |Cite
|
Sign up to set email alerts
|

Unprecedented Selectivity of Ruthenium Iodide Benzylidenes in Olefin Metathesis Reactions

Abstract: The development of selective olefin metathesis catalysts is crucial to achieving new synthetic pathways. Herein, we show that cis‐diiodo/sulfur‐chelated ruthenium benzylidenes do not react with strained cycloalkenes and internal olefins, but can effectively catalyze metathesis reactions of terminal dienes. Surprisingly, internal olefins may partake in olefin metathesis reactions once the ruthenium methylidene intermediate has been generated. This unexpected behavior allows the facile formation of strained cis‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 28 publications
(37 citation statements)
references
References 60 publications
0
37
0
Order By: Relevance
“…However, when DEDAM was mixed with DCPD in the presence of 0.5 mol % catalysts, their similar reactivity diverged. Thus, while a solution of DEDAM and DCPD with Ru‐S‐Ph‐I in hot toluene efficiently ring‐closed DEDAM leaving DCPD intact, [11] the use of Ru‐S‐CF 3 ‐I resulted in the reaction of both starting materials, even though no polymer could be detected [13] …”
Section: Figurementioning
confidence: 99%
“…However, when DEDAM was mixed with DCPD in the presence of 0.5 mol % catalysts, their similar reactivity diverged. Thus, while a solution of DEDAM and DCPD with Ru‐S‐Ph‐I in hot toluene efficiently ring‐closed DEDAM leaving DCPD intact, [11] the use of Ru‐S‐CF 3 ‐I resulted in the reaction of both starting materials, even though no polymer could be detected [13] …”
Section: Figurementioning
confidence: 99%
“…The fact that 23 could easily catalyze RCM but could not initiate ROMP of a reactive monomer led us to investigate this unique reactivity. 25 In fact, this reactivity is so unusual that it took many repetitions of the experiments by Noy Nechmad to actually convince her supervisor that this was truly happening! Thus, other ROMP monomers were also investigated and found to be completely inert (COE, COD, DCPD, norbornene dicarboxylate, and norbornene anhydride) when mixed with 23.…”
Section: Account Synlettmentioning
confidence: 97%
“…We previously reported that addition of a chloride salt to a mixture of DCPD and Ru-S-Ph-I initiated an anionic ligand exchange that induced fast polymerization. [11] Hence, a photochemical induced anion exchange could be very attractive in this case to expand photochemical prospects. An efficient chloride photocage molecule, 8-(chloromethyl)-4,4-difluoro-1, 3,5,7-tetramethyl-4-bora-3a,4a diaza-s-indacene (Cl-BODIPY), has been developed by Winter and co-workers.…”
Section: Zuschriftenmentioning
confidence: 99%
“…As expected, both Ru-S-Ph-I and Ru-S-CF 3 -I could efficiently catalyze ring-closing metathesis (RCM) reactions of diethyl diallylmalonate (DEDAM) when heated but were completely inert towards dicyclopentadiene [*] N. B. Nechmad, [+] V. Kobernik, [+] (DCPD) (see SI and ref. [11]). However, when DEDAM was mixed with DCPD in the presence of 0.5 mol % catalysts, their similar reactivity diverged.…”
mentioning
confidence: 99%